Employability skills of vocational school students in Palu City for entering the work world - Pusriawan Pusriawan; Sunaryo Soenarto (Jurnal Pendidikan Vokasi, 2019)
This study aims to determine how much the level of employability skills of students of State Vocational Schools in Palu City. This type of research is a type of survey that is to describe the attitudes, behaviors, and opinions of students' research employability skills using a quantitative deskriptive approach, then the results of data analysis are described qualitatively, then presented in graphs, diagrams, tables, mean, modes, medians, standard deviation and variant. The population in this study was 1,275 students with a study sample of 295 students. The data collection technique used is using a questionnaire. The results of the study indicate that the level of employability skills of vocational students in Palu is generally categorized as very high. The high level of employability skills of students in the State Vocational School in Palu should be a supporting factor for students to get decent work and in accordance with their competency skills so that stakeholders, especially the school must really use it well.